In vitro and In vivo Assessments on Nutraceutical and Safety of Herb-Fruit Based Drink on Female Wistar Rats - Abdul Hamid, Siti Noorwanie; Zakaria, Nor Hafizah; Abdul Majid, Fadzilah Adibah; Awang, Anis Fadhlina Izyani; Zainol, Siti Nurazwa; Zainudin, Ain Nabihah; Muhamad, Siti Nur Hidayah (IIUM Medical Journal Malaysia, 2023)
INTRODUCTION: The study aimed to assess the safety and nutraceutical properties of ALLURATM related to women’s health and skin beautification. MATERIALS AND METHODS: Determinations of total phenolic (TPC) and flavonoid contents (TFC) were done using the colorimetric method, followed by the identification of gallic acid via highperformance liquid chromatography (HPLC). Antioxidant activity was analyzed using 2,2 -diphenyl-2-picrylhydrazyl (DPPH) and 2,2’-azino-bis(3-ethylbenzthiazoline-6-sulphonic acid (ABTS) radicals while its anti-inflammatory activity was measured using enzymelinked immunosorbent assay (ELISA). Anti-aging and whitening effects were determined by porcine elastase and mushroom tyrosinase activities, respectively. Skin cell growth promotion and rejuvenation were evaluated using in vitro scratch assay. Cytotoxicity assay was done using HSF1184 and 3T3 BALB/c cell lines. While, acute toxicity test was done on two groups (control and treatment) of six Wistar rats each. The nutraceutical properties were evaluated based on proximate analysis. RESULTS: ALLURATM exhibited DPPH-IC50 values of 180.40 µg/mL and ABTS-IC50 value of 174.40 µg/mL. TPC and TFC were 67.31 mg GAE/g extract and 43.21 mg CE/g extract, respectively while 10.98 mg/g of gallic acid were quantified. ALLURATM reduced pro-inflammatory cytokines of TNF-α and IL-6 and showed anti-aging (IC50-162.40 µg/mL) and whitening effects (IC50- 167.70 µg/mL). ALLURA™ also increased the proliferation of HSF1184 (≤ 1000 µg/ mL), producing significant secretion of epidermal growth factor (EGF) and shown to be non-cytotoxic. No mortality was observed at the highest dose of 2000 mg/kg b.w.t. nor the behavioral and morphological changes in rats. The proximate analysis resulted in high content of moisture and low calories. CONCLUSION: These findings provided preliminary reports for the first time on the functionality of ALLURA™ for its anti-inflammatory, antioxidant, and nutraceutical properties.